M*A*S*H. Season nine [videorecording (DVD)] - Metcalfe, Burt; Alda, Alan, 1936-; Swit, Loretta; Morgan, Harry, 1915-2011; Gelbart, Larry (20th Century Fox Home Entertainment, 2005)
More adventures for the doctors and nurses of the 4077th unit during the Korean War. Includes all 20 episodes from the 9th season, 1980-1981.